(untitled) (Revista Contexto & Educação, 2026)
The objective of this article is to analyze the insertion of the issues of gender, women and patriarchy in the new collection from publisher Moderna aimed at High School, for the area of ​​Applied Human and Social Sciences, within the scope of history teaching. The Moderna Plus collection was chosen because it was the second most acquired by the Federal Government within the scope of the PNLD of 2021. Given the advancement of neoconservative agendas, especially from anti-gender policies, this debate becomes relevant in the context of History Teaching. The research is based on the following questions: how is the debate about gender included in the textbook? And how are women represented in the new didactic collections of Applied Human and Social Sciences that emerged in front of the BNCC and the new High School? We start from the hypothesis that, despite intense debates in the historiographical sphere, women continue to be portrayed only as participants in history, not as an object problematized based on the historical exclusion to which they were subjected. As a methodology, we chose to use Content Analysis based on data provided by the Voyant Tools tool, in which the works were inserted for analysis. It is possible to conclude, based on the data collected, that the area of ​​History contributed little to the contextualization of the theme, even given the advancement of historiography in relation to the objects studied here.